2014
DOI: 10.1016/j.exer.2014.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Does estrogen deficiency cause lacrimal gland inflammation and aqueous-deficient dry eye in mice?

Abstract: Researchers have proposed that estrogen deficiency will lead to a Sjögren's syndrome (SjS)-like lacrimal gland inflammation, aqueous tear deficiency and dry eye. The purpose of this study was to determine whether this proposal is correct. Lacrimal glands were obtained from adult, age-matched wild type (WT) and aromatase knockout (ArKO) mice, in which estrogen synthesis is completely eliminated. Tissues were also obtained from autoimmune MRL/Mp-lpr/lpr (MRL/lpr) mice as inflammation controls. Tear volumes in WT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…As shown in Table 4 , relatively few genes displaying sex-related differences were expressed by both microarrays. These findings are consistent with our previous investigations, 15 17 as well as those of others, 18 21 which discovered little agreement between CodeLink and Affymetrix microarrays in the detection of differential gene expression. Although these platforms seem to measure different things, 20 most gene expression changes revealed by each of the platforms are thought to be biologically correct.…”
Section: Resultssupporting
confidence: 93%
“…As shown in Table 4 , relatively few genes displaying sex-related differences were expressed by both microarrays. These findings are consistent with our previous investigations, 15 17 as well as those of others, 18 21 which discovered little agreement between CodeLink and Affymetrix microarrays in the detection of differential gene expression. Although these platforms seem to measure different things, 20 most gene expression changes revealed by each of the platforms are thought to be biologically correct.…”
Section: Resultssupporting
confidence: 93%
“…Surprisingly, a recent study using young ArKO mice demonstrated contradictory results, reporting that estrogen deficiency did not lead to a SjS-like inflammation in the lacrimal tissue or to an aqueous-deficient dry eye although estrogen deficiency influenced the expression of sex- and genotype-specific lacrimal gland genes [141]. This study indicates that estrogen deficiency alone may not be sufficient to induce lacrimal pathophysiology especially at a young age.…”
Section: Mouse Modelsmentioning
confidence: 84%
“…As we30,3335 and other investigators3639 have discovered, the vast majority of lacrimal gland genes in MRL/lpr and NOD female mice, which were identified as differentially expressed by the CL and Affy microarrays, were unique to each platform. Indeed, as demonstrated in Table 4, only 8.5% to 11.1% (T>P), and 7.3% to 16.8% (P>T) of the regulated genes were found by both microarrays.…”
Section: Resultsmentioning
confidence: 75%